Study of the Possibilities of the Resource Network for the Development of an Inclusive Educational Environment - Samsonova, E.V.; Bystrova, Yu.A. (Bulletin of Practical Psychology of Education, 2023)
The article presents an analysis of the results of a study devoted to the study of the issues of network interaction of educational institutions with other organizations in order to provide resource support for the development of an inclusive educational environment (IEE). The sample consisted of 274,670 people (administration; teachers; parents; students) from 1539 educational institutions (EIs). We used survey methods, analysis of the best practices of the regions, a comparative analysis of the answers of all groups of respondents, the index method. The resources and deficits of the EIs were determined for individual components of the IEE: organizational and managerial, program-methodical, subject-spatial, informational and social; the analysis and systematization of the experience of regional resource networks for the development of inclusion was carried out. Resource interaction for replenishing deficits is at a critical level for 50% EIs, at an acceptable level for 40%, and at an optimal level for 10%. A low indicator of the interaction of EIs of all levels of education with social partners (0.13) and other organizations (0.36), as well as a low level of interaction between the support team specialists within the organization (0.13) was revealed. This indicates the need to coordinate the creation of a resource network, including, among other things, NGOs and public organizations that are resource for the development of inclusion. В работе представлены результаты исследования, посвященного изучению вопросов сетевого взаимодействия образовательных организаций с иными организациями - с целью ресурсного обеспечения развития инклюзивной образовательной среды (ИОС). Выборка составила 274 670 человек (администрация; педагоги; родители; студенты СПО) из 1539 образовательных организаций (ОО). Использовались методы опроса, анализа передового опыта регионов, сравнительно-сопоставительный анализ ответов всех групп респондентов, индексный метод. Определялись ресурсы и дефициты ОО по отдельным компонентам ИОС: организационно-управленческому, программно-методическому, предметно-пространственному, информационному и социальному; проведен анализ и систематизация опыта деятельности региональных ресурсных сетей по развитию инклюзии. Ресурсное взаимодействие по восполнению дефицитов находится на критическом уровне у 50% ОО, на допустимом - у 40%, на оптимальном - у 10%. Выявлен низкий показатель по взаимодействию ОО всех уровней образования с социальными партнерами (0,13) и другими организациями (0,36), а также низкий уровень взаимодействия специалистов команды сопровождения внутри организации (0,13). Это указывает на необходимость координации создания ресурсной сети, включающей, в том числе, НКО и общественные организации, являющиеся ресурсными для развития инклюзии.